INVESTMENT DIVERSIFICATION AND FINANCIAL PERFORMANCE OF COMMERCIAL BANKS IN KENYA: CONTROLLING ROLE OF BANK SIZE - Ngware , Stephen Githaiga (International Journal of Accounting & Finance Review, 2025)
This study examines the connection between diversification of investments and the financial outcomes of commercial banks in Kenya, moderated by Bank size. It addresses critical issues related to portfolio diversification roadmaps within the banking sector, mainly focusing on mitigating various classes of risk. The findings aim to provide insights into best practices for risk management and strategic investment, contributing to a more resilient banking industry in Kenya. The target population for this study includes the 38 commercial banking institutions that held official licenses from the Central Bank of Kenya as of December 2023. The paper employs an analysis of unbalanced secondary panel data, which comprises both time series and cross-sectional data. Data was sourced from the Kenya National Bureau of Statistics, the World Bank, the Central Bank of Kenya, and the published financial statements of all 38 licensed commercial banks in Kenya. The data covers the period from 2013 to 2023. Investment diversification has a significant positive impact on financial performance. The study suggests that an investment portfolio is a key factor in determining the financial performance of commercial banks in Kenya. The findings indicate that diversification of investment portfolios among Kenyan banks encompasses various asset classes, including placements, shares, and government securities, as well as alternative investments, with a notable preference for government securities. Kenyan banks should actively diversify their investment portfolios by including placements, government securities, and shares to enhance their financial performance. By emphasizing the importance of strategic investment choices, particularly in government securities and shares, banks can achieve significant improvements in their overall financial outcomes. JEL Classification Codes: G32, F65, L66, L25, M41.